The impact of objective and subjective measures of air quality and noise on house prices: a multilevel approach for downtown Madrid - Coro Chasco; Julie Le Gallo (European Regional Science Association (ERSA), 2011)
Air quality is one of the major concerns in big cities. It is therefore of interest to evaluate properly air pollution. Specifically, this paper aims at measuring how air quality is incorporated in transaction prices in downtown Madrid. For that purpose, we use multilevel models since our sample is hierarchically organized into 3 levels. Our first-level consists of 5,080 house prices. The second level consists of 759 census tracts while the third level consists of 43 neighbourhoods. We have variables available for each level, individual characteristics for the first level and various socio-economic data for the other levels. The outline of the paper is as follows. First, we combine a set of noise and air pollutants measured at a number of monitoring stations available for each census tract. Second, we apply kriging to match the monitoring station records to the census data. Third, we estimate hedonic models in order to measure the marginal willingness to pay for air quality in downtown Madrid. While the conventional approach to estimate hedonic models is to use ordinary least squares, we exploit the hierarchical nature of our data and estimated multilevel models instead. These allow for a more reliable statistical inference.
Keywords: 330